SASAK WOMAN’S DIGNITY: THE REPRESENTATION OF LOMBOK IN THE NOVEL SRI RINJANI - Dharma - Satrya HD (Universitas Teknokrat Indonesia, 2021)
This article discussed about the representation of Sasak woman in a contemporary novel entitled Sri Rinjani. This article explains how Sasak women are described in the novel Sri Rinjani and explains the production source of that description. This article used representation theory which combined two approaches: semiotic approac and discursive approach. Through those two approaches, representation theory can theorize the practice of meaning production and knowledge about Sasak woman. The analysis showed that Sasak women struggle their dignity as a woman. Rinjani and Malaysia was mobilized to construct the meaning of woman. Rinjani as a Sasak’s cosmological centre was used to justify the action to struggle the dignity of Sasak woman. Dignity cannot be reached even by money. Malaysia only gave pain. Malaysia did not give happiness, but only gave pain. Sri Rinjani’s effort in achieving dignity was helped by a rich Sasak man, who was in the same age of his father. For the dignity, she marry with Pak Kamil, so the kindness was give as husband and wife. Dignity cannot be achieved by the effort of Sasak woman herself, but also by the contribution of Sasak man. The effort in achieving dignity was the construction of Sasak woman in 2000’s until now.